Analysis of the association between the acetabular morphology and femoral head in children aged 0-3 years with developmental hip dysplasia - Liukun Xu; Bo Wang; Li Wang; Zhiqun Zhang (Frontiers Media S.A., 2023)
BackgroundMagnetic resonance imaging (MRI) has been advocated as a routine examination for preoperative and postoperative assessment of Developmental Dysplasia of the Hip (DDH). However, there is limited research regarding the correlation between acetabulum and femoral head morphology using preoperative MRI measurements.ObjectiveTo explore the correlation between acetabulum and femoral head morphology in children with DDH aged 0-3 years, using MRI measurements as indicators.MethodsA Retrospective Analysis of MRI Data from 172 Children Diagnosed with Developmental Dysplasia of the Hip (DDH) at Nanjing Medical University Affiliated Children's Hospital, spanning from January 2017 to January 2022. Measurements were taken to assess various parameters reflecting hip socket morphology as well as the development status of the femoral head and ossifying nucleus. The correlation between these factors was explored using Pearson correlation analysis and multiple-factor linear regression. Statistical analysis was conducted using SPSS 18.0 software.ResultsPearson correlation analysis revealed statistically significant associations between the length of the ossifying nucleus ratio and age(mo.), BAI, BCAD, CTAD, and CTAD. The height of the ossifying nucleus ratio displayed statistically significant correlations with age(mo.) and BTAD. The length of the femoral head ratio exhibited statistically significant correlations with CAI, BCEA, and BCAD. Furthermore, the height of the femoral head ratio demonstrated a statistically significant correlation with BCEA. After adjusting for age(mo.), BMI, BCEA, and CCEA, BPoAcet and CPoAcet was found to be correlated with the length of the ossifying nucleus ratio. Preoperatively, the CAI, BAxAcet, BPoAcet, CPoAcet, and BTAD were correlated with the height of ossifying nucleus ratio after correcting for age, BMI, BCEA, and CCEA.ConclusionThe measurement parameters of hip socket morphology on MRI are associated with femoral head development, making them potential predictive indicators for femoral head development in DDH patients. These findings offer valuable insights for clinical decisions regarding the timing and approach of surgery in patients with developmental hip dislocation.